One new combination in the genus Hydrangea (Hydrangeaceae) - Deshmukh, Umakant Bhoopati; Shende, Mukund Bapurao (Phytotaxa, 2021)
The recent study on the molecular phylogenetics of the family Hydrangeaceae (Samain et al.,2010; Granados Mendoza et al., 2013; De Smet et al. 2015) revealed that eight genera Decumaria Linnaeus (1753: 397), Dichroa Loureiro (1790: 301), Broussaisia Gaudichaud (1830: 479), Schizophragma Siebold & Zuccarini (1838: 58), Platycrater Siebold & Zuccarini (1838: 62), Cardiandra Siebold & Zuccarini (1839: 119), Pileostegia Hook.f. & Thomson (1857: 57) and Deinanthe Maximowicz (1867: 2) are phylogenetically nested within Hydrangea Linnaeus (1753: 397), rendering the latter highly polyphyletic.